LF 08-0299 in the prophylaxis and treatment of chronic rejection in a rat aortic allograft model - Lácha, J; Rossmann, P; Lodererová, A; Havlíèková, J; Vítko, S (Transplant international, 2000)
Chronic rejection is the major cause of late kidney allograft failure. We evaluated the efficacy of LF 08-299 (LF), an analogue of 15-deoxyspergualin, in a rat aortic allograft model of chronic rejection. BN aortic allografts were transplanted to Lew recipients. LF was administered at a dose of 6 mg/kg and 2.5 mg/kg on days 0-20 and 6 mg/kg on days 60-90. CyA was used at a dose of 5 mg/kg on days 0-20. Untreated isografts and allografts were used as controls. Histological changes and immunohistochemistry were monitored sequentially at 8, 12, 16 and 20 weeks. There were no differences in intimal proliferation between LF-treated allografts and untreated or CyA-treated controls. Only a tendency in adventitial infiltration reduction was seen in LF-treated animals. We found a significantly less pronounced reduction in media diameter in LF-treated animals. We concluded that LF 08-0299 is only able to reverse reduction in media thickness in aortic allografts, but not intimal proliferation in this model of chronic rejection.
Keywords: aorta; potkani inbrední BN; Rats, Inbred Lew; Transplantation, Isogeneic; Chronic Disease; Dose-Response Relationship, Drug; Graft Rejection; krysa rodu Rattus; zvířata; imunosupresiva; Transplantation, Homologous; Rats, Inbred BN; Immunosuppressive Agents; cyklosporin; chronická nemoc; transplantace izogenní; potkani inbrední LEW; Rats; vztah mezi dávkou a účinkem léčiva; Cyclosporine; Animals; karbamáty; Carbamates; homologní transplantace; Aorta; rejekce štěpu